Low prevalence of hepatitis B and C infections among HIV-infected individuals in Slovenia - Seme, Katja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
BACKGROUND: With the increased lifespan of HIV-1 infected patients, mostly dueto highly active antiretroviral therapy, hepatitis C virus (HCV) and hepatitis B virus (HBV) have recently emerged as important pathogens in these patients. HIV-1 infection has an important negative impact on the natural history of HCV and HBV infections, which has consequently caused increased liverassociated and overall morbidity and mortality in HIV-1 infected patients. Thus, liver disease is currently the second leading cause of death in HIV-infected persons in Europe. OBJECTIVE: To determine the prevalence of HBV and HCV infection in HIV-infected individuals in Slovenia. METHODS AND RESULTS: 356 out of 409 Slovenian individuals, confirmed as HIV positive by the end of 2008, were tested for the presence of HBV and HCV infection. Evidence of prior and current HBV infection was found in 77 (21.6%) and 14 (3.9%) of HIV-positive patients, respectively. 38 of 356 (10.7%) HIV-infectedindividuals were confirmed as anti-HCV positive, and 26 of them (68.4%) were also HCV RNA positive. Concomitant active HBV and HCV infection was found in only two HIV-positive individuals. CONCLUSION: In a study carried out on the highest proportion per entire population of HIV-infected individuals from a certain country or geographical region, Slovenia was identified as the country with the lowest prevalence of HCV infection among HIV-infected individuals.
Keywords: Adult; Aged; Aged, 80 And Over; baby; Child; Child, Preschool; Comorbidity; Dojenček; Epidemiology; hepatitis; Hepatitis B; Hepatitis C; HIV; Hiv Infections; HIV infekcije; Infant; infekcije; Odrasli; Otrok; Otrok predšolski; Prevalenca; Prevalence; Slovenia; Slovenija; Soobolevnost; Starost 80 in več; Starostniki